College Algebra & Trigonometry - Beveridge, Richard W.; Open Textbook Library (Open Textbook Library, 2018)
This College Algebra text will cover a combination of classical algebra and analytic geometry, with an introduction to the transcendental exponential and logarithmic functions. If mathematics is the language of science, then algebra is the grammar of that language. Like grammar, algebra provides a structure to mathematical notation, in addition to its uses in problem solving and its ability to change the appearance of an expression without changing the value.
1 Algebra Review -- 2 Polynomial and Rational Functions -- 3 Exponents and Logarithms -- 4 Functions -- 5 Conic Sections - Circle and Parabola -- 6 Sequences and Series -- 7 Combinatorics -- 8 Right Triangle Trigonometry -- 9 Graphing the Trigonometric Functions -- 10 Trigonometric Identities and Equations -- 11 The Law of Sines The Law of Cosines
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks